The development of video learning media on cell division subtopic for ninth grade students - F. Fitriyani; Ruqiah Ganda Putri Panjaitan; T. Titin; Zhu Caiping (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
The cell division process that occurs within the body cannot be directly observed, making the cell division material difficult to learn. Difficulties in studying cell division material can be aided by using learning media that can visualize the material effectively. The objective of this research is to develop science learning videos on the subtopic of cell division for Grade IX and to assess their suitability as learning media. This research adopts a Research and Development (R&D) methodology with five stages including potential and problems, data collection, product design, design validation, and design revision. The subjects in this research are validators from the field of biology expertise. The instrument used for data collection is the validation sheet. The data analysis techniques employed include qualitative data analysis and quantitative data analysis. The results of this research obtained CVR and CVI values of 1.00 with a valid category, indicating that the developed science learning videos on the subtopic of cell division are suitable for use in learning. Therefore, this learning media can be a recommendation in the learning process on subtopic cell division.